2004
DOI: 10.1088/0268-1242/19/9/002
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of solar cell degradation in space from the electron–proton equivalence

Abstract: From a comparison between the degradation rates, induced by proton and electron irradiations, of the performances of GaAs quantum well based vertical cavity surface emitting laser, we deduce a coefficient of equivalence between the two types of irradiations. This coefficient allows us to calculate the fluence of protons of a given energy which produces the same degradation as a fluence of electrons of a standard energy. We apply the result of this analysis to the degradation of GaAs solar cells, demonstrating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…Studies necessary to get all the necessary data (in unirradiated as well as irradiated materials) for GaAs and GaInP materials have been systematically performed over years: from 1985 to 2005 for GaAs [1][2][3][4][6][7][8]12,19,20,[22][23][24] and from 1998 to 2003 for GaInP [2,5,7,8,[18][19][20]23]. The DLTS technique provides only an order of magnitude for s (through extrapolation to infinite temperature T of the plot log e n versus 1/T determined in a narrow temperature range).…”
Section: Measurements Of the Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies necessary to get all the necessary data (in unirradiated as well as irradiated materials) for GaAs and GaInP materials have been systematically performed over years: from 1985 to 2005 for GaAs [1][2][3][4][6][7][8]12,19,20,[22][23][24] and from 1998 to 2003 for GaInP [2,5,7,8,[18][19][20]23]. The DLTS technique provides only an order of magnitude for s (through extrapolation to infinite temperature T of the plot log e n versus 1/T determined in a narrow temperature range).…”
Section: Measurements Of the Parametersmentioning
confidence: 99%
“…This concept is valid in the cases of GaAs and GaInP cells [12] because: (i) the defects created by energetic electrons and protons are the same, since they result directly from the transmission of energy to the ''primary knock-on atom'' and (ii) the displaced atoms, which are stable at room temperature, are separated by an average distance larger than the extension in space of their wave functions in the case of proton irradiation so that they are isolated, like in case of electron irradiation. This is not true for Si because the primary defects, interstitials and vacancies are mobile at room temperature and form complexes with impurities (doping or native) and between themselves.…”
Section: Introductionmentioning
confidence: 97%
“…It was observed that the space solar figures of merit (the short circuit current , the open circuit voltage , the maximum output power , the fill factor and the conversion efficiency ) decrease linearly with the logarithm of the fluence. The degradation was analytically modeled [10][11][12][13][14] in order to predict the effect of the long term exposure of the solar cells [15,16]. For example, is related to the irradiation fluence by a simple formula of the form [17]:…”
Section: Introductionmentioning
confidence: 99%
“…Various defects are created under an irradiation and only a fraction of them behaves as recombination centers. This introduction rate depends on the material and the energy of the incident particles [17].…”
Section: Equationsmentioning
confidence: 99%